2017
DOI: 10.1016/j.neuron.2017.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-2/PlexinA3 Receptors Associate with GluA1 and Mediate Sema3F-Dependent Homeostatic Scaling in Cortical Neurons

Abstract: SUMMARY Regulation of AMPA-type glutamate receptor (AMPAR) number at synapses is a major mechanism for controlling synaptic strength during homeostatic scaling in response to global changes in neural activity. We show that the secreted guidance cue semaphorin 3F (Sema3F) and its neuropilin-2 (Npn-2)/plexinA3 (PlexA3) holoreceptor mediate homeostatic plasticity in cortical neurons. Sema3F-Npn-2/PlexA3 signaling is essential for cell surface AMPAR homeostatic downscaling in response to an increase in neuronal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 52 publications
4
66
0
Order By: Relevance
“…The neuronal pentraxin family of proteins interacts with the AMPAR N-terminal domain (118), with critical roles in maintaining synaptic AMPAR content in inhibitory interneurons (119) and retinal ganglion cells (120), but not CA1 pyramidal neurons (121). Neuropilin-2 binds to the extracellular N terminus of GluA1 through its two CUB domains (122), which is noteworthy because two different CUB domain-containing proteins, SOL-1 and SOL-2, have been identified as critical for functional surface expression of AMPARs in Caenorhabditis elegans (123,124). Moreover, two other CUB domain-containing proteins, NETO-1 and NETO-2, are auxiliary subunits of kainate receptors, which constitute another group of ionotropic glutamate receptor homologous AMPARs (125,126).…”
Section: Postsynaptic Anchoring Of Ampars By -Actininmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuronal pentraxin family of proteins interacts with the AMPAR N-terminal domain (118), with critical roles in maintaining synaptic AMPAR content in inhibitory interneurons (119) and retinal ganglion cells (120), but not CA1 pyramidal neurons (121). Neuropilin-2 binds to the extracellular N terminus of GluA1 through its two CUB domains (122), which is noteworthy because two different CUB domain-containing proteins, SOL-1 and SOL-2, have been identified as critical for functional surface expression of AMPARs in Caenorhabditis elegans (123,124). Moreover, two other CUB domain-containing proteins, NETO-1 and NETO-2, are auxiliary subunits of kainate receptors, which constitute another group of ionotropic glutamate receptor homologous AMPARs (125,126).…”
Section: Postsynaptic Anchoring Of Ampars By -Actininmentioning
confidence: 99%
“…Moreover, two other CUB domain-containing proteins, NETO-1 and NETO-2, are auxiliary subunits of kainate receptors, which constitute another group of ionotropic glutamate receptor homologous AMPARs (125,126). The neuropilin-2-GluA1 interaction is disrupted upon increased neuronal network activity in hippocampal cultures because of the activity-induced secretion of the neuropilin-2 agonist semaphorin 3F (122). This reduction in postsynaptic response depends on the Ras guanosine triphosphatase activating protein (GAP) activity of the cytosolic C terminus of PlexinA3, which dimerizes with neuropilin-2 in the AMPAR complex.…”
Section: Postsynaptic Anchoring Of Ampars By -Actininmentioning
confidence: 99%
“…Indeed, the related semaphorin Sema3E is present in the developing striatum and signals through PlexinD1 to establish thalamostriatal synapses on direct pathway SPNs (Ding et al, 2012). Furthermore, semaphorins have a recently described role in various forms of adult synaptic plasticity (Orr et al, 2017;Wang et al, 2017). Finally, semaphorin signaling could influence corticostriatal synapses by altering excitatory synapse formation in apical dendrites of Layer V neurons, which may have downstream effects on the corticostriatal synapse (Kozorovitskiy et al, 2012;Peixoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, expression of PHP requires molecules that regulate vesicle release and the RRP size, such as RIM , Rab3-GAP (Muller et al, 2011), Dysbindin (Dickman and Davis, 2009), SNAP25 and Snapin (Dickman et al, 2012). Recent studies demonstrated that transsynaptic Semaphorin/Plexin interactions control synaptic scaling in cortical neurons in vertebrates (Wang et al, 2017) but also drive PHP at the fly NMJ (Orr et al, 2017). Neto-α may interact with one or several such presynaptic molecules and function as an effector of PHP.…”
Section: Discussionmentioning
confidence: 99%